Infrared spectrum and UV-induced photochemistry of matrix-isolated 5-methoxy-1-phenyl-1H-tetrazole - Gómez-Zavaglia, Andrea (2006)
The molecular structure, vibrational spectra and photochemistry of 5-methoxy-1-phenyl-1H-tetrazole (5MPT) were studied by matrix isolation infrared spectroscopy and DFT(B3LYP)/6-311++G(d,p) calculations. According to the calculations, only one double degenerated-by-symmetry minimum exists in the ground state PES of the compound. In this structure, the dihedral angle between the two rings (phenyl and tetrazole) is ca. 30°, whereas the methoxyl group stays nearly in the plane of the tetrazole ring. In consonance with the theoretical predictions, only one molecular species was experimentally observed in the as-deposited argon matrices. Theoretical calculations were also used to help in assignment of the experimental spectrum of the compound, the calculated spectrum showing a very good agreement with the experimental data. In situ UV-irradiation ([lambda] > 235 nm) of the matrix-isolated 5MPT induced unimolecular decomposition of the compound, which led mainly to production of methylcyanate and phenylazide, this latter further reacting to yield, as final product, 1-aza-1,2,4,6-cycloheptatetraene. 3-Methoxy-1-phenyl-1H-diazirene was also observed experimentally as minor product, resulting from direct elimination of molecular nitrogen from 5MPT.